Global Terror and the Rise of Xenophobia/ Islamophobia: An Analysis of American Cultural Production since September 11 - Awan, Muhammad Safeer (Islamic Studies, 2010)
There are thirty-three verses of the Holy Qur’┐n and numerous references to other theological sources of Islam in the novel Terrorist published in 2006 by the American novelist John Updike (1932–2009). Updike is not the only writer who has contributed in the post-9/11 American cultural production by relying on the same websites of Qur’anic pseudo-scholarship as did Don Delillo, Martin Amis and others. With the rise of global terror, the world witnessed a steep rise in such psycho-social and political phenomena as xenophobia in general and Islamophobia in particular. So much so that even the novelists, filmmakers, producers, and photographers lost their sense of justice and balance. This paper is about the stereotypical representations of the Muslim as a community and Islam as a faith in the post-9/11 American popular cultural production, with focus on some novels and short stories, particularly Updike’s Terrorist. The researcher has made an attempt at exploring the possible motives of the author for excessive quotations from the Holy Qur’an and their operational purpose in the overall settings of the novel. Examples of stereotyping and misrepresentation have been explored in view of the schematic plot that not only shows extreme religiosity of the protagonist Ahmad Mulloy but also portrays him imitating the actions of the actual perpetrators of 9/11 attacks. The paper attempts to explore the politics of cultural production in times of security panic that often leads to moral crises. At the same time, it presents a contrasting balance in narrative by comparing Updike’s novel with Mohsin Hamid’s The Reluctant Fundamentalist (2007).